TOURISM, NATURAL PROTECTED AREAS, CONSERVATION, LAND MANAGEMENT, COSTA RICA - Quirós-Arias, Lilliam (2017)
Ever since the 1980s, conservation-related tourism has been particularly important in Costa Rica. The interest in enjoying and being part of nature brought a signifcant change to how tourism is practiced. The country hosts a great wealth of natural and cultural resources, as well as rural landscapes characterized by protected areas and surrounded by natural landscapes and local communities. This document reviews the experience of Santa Rosa National Park, located in the Guanacaste Conservation Area (ACG)—an area with emerging tourism development and naturalattractions as its main resource. The participation and integration of local communities are part of recent concerns. Our methodology includes a review of secondary information and frst-person interviews with townspeople. Moreover, information was gathered on-site through different visits to the area of study. The ACG is one of the protected areas that hosts important resources for research;however, increasing conservation in neighboring areas and incorporating the local community still represents a challenge.